NALANDA ‘SCHOOL OF JOY’: TEACHING LEARNING STRATEGIES AND SUPPORT SYSTEM, FOR IMPLEMENTING CHILD FRIENDLY EDUCATION IN BANGLADESH - Ferdousi, Sufia (PEOPLE: International Journal of Social Sciences, 2018)
Child-friendly education (CFE) is very important for the children, especially the early year’s students, because it fosters the holistic development of a child. Teacher plays a key role for creating child friendly education. This study intends to learn about child friendly education in Bangladesh. The purpose of the study is to explore how CFE is being practiced in BangladeshOne school, named Nalanda, was selected for the study as it claims to run the school through CFE approach. The objective of the study was to identify, how this school is different from the other schools in Bangladesh, to explore overall teaching learning system like, curriculum, teaching strategies, assessments and to investigate the support system for Child Friendly Education provided to the teachers through training or mentoring. The nature of the case study was qualitative method to get maximum information from the students, parents, teachers and school authorities. The findings were based on 3 classroom observations, interviews with 1 teacher, 1 head teacher and 1 trainer, FGD with 10 students and 6 parents, were used to collect the data. It has been found that Nalanda is different than the other schools in Bangladesh in terms of, parents’ motivation about school curriculum, and sufficiency of teachers’ knowledge on joyful learning/child-friendly learning. Teachers showed particular strength in the teaching learning strategies, using materials and assessment. And Nalanda gives strong support for teacher’s training. In conclusion, The Nalanda School in Dhaka was found appropriate for the requirements of Child-friendly education.